2013
DOI: 10.1667/rr3082.1
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 -Treg Cells Enhanced by Repeated Low-Dose Gamma-Irradiation Attenuate Ovalbumin-Induced Allergic Asthma in Mice

Abstract: Gamma radiation is used for several therapeutic indications such as cancers and autoimmune diseases. Low-dose whole-body γ irradiation has been shown to activate immune responses in several ways, however, the effect and mechanism of irradiation on allergic asthma remains poorly understood. This study investigated whether or not irradiation exacerbates allergic asthma responses and its potential mechanism. C57BL/6 mice were sensitized and challenged with ovalbumin (OVA) to induce asthma. The mice received whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 60 publications
1
32
1
Order By: Relevance
“…The dose of radiation exposure was determined in accordance with ''The radioactive half-life table'' provided by the irradiator company (22). org/10.1667/RR13547.1.S1).…”
Section: Preparation and Activation Of Bone Marrow-derived Mast Cellsmentioning
confidence: 99%
“…The dose of radiation exposure was determined in accordance with ''The radioactive half-life table'' provided by the irradiator company (22). org/10.1667/RR13547.1.S1).…”
Section: Preparation and Activation Of Bone Marrow-derived Mast Cellsmentioning
confidence: 99%
“…There were no data concerning Treg cells in the above three reports; however, the Treg population in asthma mice model was recently reported by Park et al (2013a). They showed the Treg cell population was higher in irradiated OVA mice than in OVA or control mice.…”
Section: T-cell Subpopulationsmentioning
confidence: 88%
“…They suggested that Treg cells enhancement/migration by irradiation may exert a suppressive function in airway inflammation and tissue remodeling in allergic N. Shimura and S. Kojima asthma. Their irradiation protocol of Park et al (2013a) (Fig. 7) was completely different from that of Fang et al (2005) (Fig.…”
Section: T-cell Subpopulationsmentioning
confidence: 99%
“…In human allergy patients, Treg cell numbers decrease in the peripheral blood and BALF, and cannot suppress the cell proliferation and cytokine production of allergen-stimulated CD4 + T cells (2426). Furthermore, several murine studies have demonstrated that the induction of Treg cell function reverses the airway hyperresponsiveness and protects against experimentally-induced asthma (27,28). In the current study, the results of flow cytometric analysis revealed that OVA challenge was able to significant increase the proportion of Th17 cells and decrease the proportion of Treg cells, resulting in imbalance of the Th17/Treg cell ratio; this suggests that the Th17/Treg imbalance serves an important role in the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 99%